2018
DOI: 10.1257/mac.20140181
|View full text |Cite
|
Sign up to set email alerts
|

The Firm Size Distribution across Countries and Skill-Biased Change in Entrepreneurial Technology

Abstract: Development is associated with systematic changes in the firm size distribution. I document that the mean and dispersion of firm size are larger in rich countries, and increased over time for US firms. To analyze the firm size-development link, I construct a frictionless general equilibrium model of occupational choice with skill-biased change in entrepreneurial technology (i.e., technical progress favors better entrepreneurs). The model accounts for key aspects of the US experience with only changes in aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
82
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 59 publications
11
82
0
2
Order By: Relevance
“…Assuming a correlation between energy use and GDP, then the evidence presented here is consistent with previous research that has focused on the relation between firm size and GDP per capita [18,20,[29][30][31]. However, my focus here on energy use (rather than GDP) is intentional: it is part of a larger effort to ground economic theory in the laws of thermodynamics [32], and to root empirical analysis in biophysical (rather than monetary) phenomena [33][34][35][36].…”
Section: The Mean Firm Size Increases;supporting
confidence: 88%
“…Assuming a correlation between energy use and GDP, then the evidence presented here is consistent with previous research that has focused on the relation between firm size and GDP per capita [18,20,[29][30][31]. However, my focus here on energy use (rather than GDP) is intentional: it is part of a larger effort to ground economic theory in the laws of thermodynamics [32], and to root empirical analysis in biophysical (rather than monetary) phenomena [33][34][35][36].…”
Section: The Mean Firm Size Increases;supporting
confidence: 88%
“…Hsieh and Klenow [2009] consider how distortions affecting marginal products of labor and capital lead to a departure from an efficient firm size distribution. Other explanations rely on policy aspects (e.g., Guner et al [2008]), institutions (e.g., Grobovsec [2013]), or technology (e.g., Poschke [2011]). Antunes and Cavalcanti [2007] and Amaral and Quintin [2006] highlight the role of informality in Latin America.…”
mentioning
confidence: 99%
“…We consider two measures of educational attainment: completed secondary education and some college, and completed tertiary education. According to Poschke [2011], there is a strong relationship between the average firm size in a country and its income per capita. We therefore control for the log of GDP per capita and the log of the population size.…”
mentioning
confidence: 99%
“…Finally, as discussed by Poschke (2015), the average size of firms increased substantially in the last century, as did their dispersion -increasing the skewness of the size distribution. Figure 10b plots the average of both the within run average and standard deviation of firms across 25 replications.…”
mentioning
confidence: 89%
“…A trend common to both these aspects is the increasing firm's size. It has been shown that average firm size increases with national per capita income (Poschke, 2015) and market concentration (The Economist, 2016), and is correlated to wage dispersion (Mueller et al, 2015) and CEOs' pay rises (Frydman and Jenter, 2010). OECD (2017) suggests that recent innovations have increased market concentration and that the innovation rents have been redistributed to shareholders and managers.…”
Section: Introductionmentioning
confidence: 99%